Evaluasi Manajemen Logistik Obat di Instalasi Farmasi Dinas Kesehatan Kota Kendari Tahun 2021 - Tasrim, Indriani; Hasanuddin, Silviana; Fitrawan, La Ode Muh.; Adlu, La Ode Muhammad (Jurnal Pharmacia Mandala Waluya, 2024)
Drug logistics management is a series of activities involving aspects of planning, procurement, storage, distribution and elimination of drugs as well as recording and reporting of drugs that are managed optimally to achieve the accuracy of the total of drugs, types of drugs and health supplies. This study aimed to evaluate the drug logistics management at the Pharmacy Installation in Health Office of Kendary City in 2021. The type of study was a descriptive-evaluative research . The population amounted to 4 informants , and the data was collected through observation and interviews. The qualitative data was analyzed in textual form in the form of narratives, while quantitative data was calculated using Microsoft Office Excel 2010. The calculation results were described in the form of tables, and percentages, and then analyzed based on predetermined indicators. The results of the study showed that the logistics management at the Pharmacy Installation in the Health Office of Kendari City in 2021 at the planning stage was according to the standard of 77.13%, at the procurement stage, it was not according to the standard of drug availability indicators in accordance with the needs of 46%, the procurement of generic drugs 99.13 %, at the drug storage stage was not according to the standard, where the Conformity Between Drugs and Card Stock indikators was 100%, Turn Over Ratio (TOR) was 0.61 times, the percentage of dead stock was 1.14%. Moreover, the distribution stage was 100%, the accuracy of LPLPO time was 100%, and the drug void time was 2.81%. The elimination and destruction of drugs were in accordance with the standards of the Regulation of the Food and Drug Supervisory Agency no. 14 of 2019, and the stages of recording and reporting drugs were in accordance with the standards of the 2010 Minister of Health Regulation. This study hoped there will be improvements in drug logistics management at the Pharmacy Installation in the Health Office of Kendary City so that all assessment indicators meet the applicable standard values and realize effective and efficient drug management